The Application of Autogenic Relaxation Techniques in Elderly People with Type II Diabetes Mellitus to Stabilize Blood Glucose Levels - Dwi Aprilia, Ergi; Antika, Dwi; Sutrisno; Rice, Hernanda (INDOGENIUS, 2025)
Background & Objective: Diabetes (DM) is a type of metabolic disorder caused by abnormal insulin production, insulin performance, or a combination of both, characterized by elevated blood sugar levels. The objective of this study was to determine the effects of autogenic relaxation techniques on elderly people with type 2 diabetes. Method: This study employed a single-group pretest-posttest design in a quasi-experimental setting. The study included 15 participants with diabetes mellitus, selected using purposive sampling. The case study was conducted from April 25 to 27, 2025, over three sessions of 15 minutes each. Blood sugar levels were measured using a glucometer before and after the intervention. Data analysis was performed using a paired t-test to compare average blood sugar levels before and after the autogenic relaxation technique. Result: Before and after the intervention, the average blood sugar levels were 257 mg/dl and 234 mg/dl, respectively. The average age of the respondents was 70 years, and they had been living with diabetes mellitus for more than five years. Before and after the autogenic relaxation intervention, blood sugar levels changed with a p-value of 0.000 based on the paired t-test. Conclusion: Autogenic relaxation can lower blood glucose levels.